A COMPARATIVE STUDY OF TOTAL THORACOSCOPIC AORTIC VALVE SURGERY AND TRADITIONAL OPEN-CHEST AORTIC VALVE SURGERY: A PROPENSITY SCORE-MATCHED STUDY: Total thoracoscopic aortic valve surgery - Xiaofei Zhang, Bin Ni (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Research aim: By collecting and analyzing the clinical data of total thoracoscopic aortic valve replacement, and comparing it with the relevant data of traditional midline thoracotomy aortic valve replacement, in order to ensure the accuracy of the comparison, the study adopted sophisticated propensity score matching technology. To identify the significant advantages and unique features of total thoracoscopic surgery. In addition, this study also included a detailed compilation and analysis of domestic and foreign literature on minimally invasive aortic valve replacement surgery, compared the application effects of different minimally invasive surgical methods in clinical practice, and in-depth analysis of the advantages and disadvantages. These research results provide important reference for the promotion and application of total thoracoscopic surgery in clinical practice. To scientifically evaluate the feasibility, safety, minimally invasive and cosmetic effects of total thoracoscopic technology in aortic valve replacement. Verify the reliability of the total thoracoscopic heart valve surgery model and the surgical operation specifications and clinical treatment standards, and lay a theoretical and clinical foundation for the application and promotion of total thoracoscopic technology in cardiac surgery. Research methods: Selected patients: We screened a total of 24 eligible patients in the thoracoscopic group who underwent thoracoscopic surgery in our hospital from January 2020 to December 2023, and 366 patients who underwent traditional median sternotomy aortic valve replacement. By propensity score matching, 24 patients in the total thoracoscopic aortic valve replacement group were compared with 24 patients in the traditional midline thoracotomy group (control group). Surgical technique: 1.1 Anesthesia management: same as mitral valve. 1.2 Establishment of peripheral extracorporeal circulation: same as mitral valve. 1.3 Surgical method: 1.3.1 Setting of three holes on the chest wall: The first hole is the entry hole for the left hand instrument, 1 to 2 cm long, located between the anterior axillary line and the mid-axillary line on the right side of the third intercostal space. The second hole is the right-hand instrument entrance hole, 2.5-3 cm long, located between the midclavicular line and the anterior axillary line. The third hole is the thoracoscopic entrance, located at the junction of the anterior axillary line and the mid-axillary line in the fourth intercostal space on the right side, and is about 1.5-2cm long. 1.3.2 The sequence of three-port incision is as follows: Same as the mitral valve. 1.3.3 Pericardial incision and suspension: same as mitral valve. 1.3.4 Place left ventricular drainage: same as mitral valve. 1.3.5 Insert the perfusion tube into the aortic root: same as the mitral valve. 1.3.6 Block the ascending aorta: Insert the aorta blocking forceps into the operating hole of the left hand. Myocardial protective solution can be injected through the aortic root, and this method is suitable for perfusion in patients with aortic valve stenosis. 1.3.7 Perfuse the left and right coronary arteries separately under direct vision: For patients with aortic regurgitation, use an oblique incision near the aortic root, about 1.5-2 cm from the front wall of the aorta, and observe the openings of the left and right coronary arteries. , and then use a three-way perfusion tube to perfuse the left and right coronary arteries simultaneously. 1.3.8 Aortic incision and traction: Gradually extend the aortic incision from the left side to above the junction of the left and right coronary arteries, and then further expand to the right. Near the border of the left coronary sinus, the surgical team will A 5-0 Prolene suture is applied to the center of the upper end and combined with a spacer for lifting. This step is to properly draw the incision edge superiorly and to the right and ensure that it is stably attached to the inferior right edge of the pericardiotomy area. At the same time, 5-0 Prolene sutures and spacers were also used for suspension on both sides of the lower end of the aortic incision, and were respectively pulled and safely fixed on the left edge of the pericardiotomy and the surface of the diaphragm to ensure the stability of the incision. 1.3.9 Treatment of the aortic valve: Use a 2/0 double-ended needle with a gasket, place the gasket on the left ventricular side or aortic side of the aortic valve annulus, and perform mattress-style interrupted sutures along the aortic valve annulus. The order of suturing is first the right coronary annulus, then the left coronary annulus, and finally the non-coronary annulus. All sutures are pulled out through the right-hand operating hole and evenly stuck on the wire clamping ring. After the external thoracic valve is sutured, they are inserted into the aortic valve annulus through the right-hand operating hole and tied and fixed with a special knotter. The aortic incision is sutured with 4-0 Prolene sutures with pads using a combination of mattress and continuous methods to reduce incisional bleeding. Research result: After propensity score matching, there was no significant statistical difference in the basic data between the total thoracoscopy group and the control group. The results of the study showed that compared with traditional open surgery, the average operation time of the total thoracoscopic AVR group increased (188.39±41.78 vs. 169.93±43.56, p=0.0027). Similarly, the average cardiopulmonary bypass time and aortic cross-clamping time in the thoracoscopic group were significantly longer than those in the control group (179.87±47.65min vs. 109.47±19.46min, p<0.0001; 119.53±30.89min vs.68.12±18.08min, p <0.0001. Moreover, the proportion of patients in the thoracoscopic AVR group with extracorporeal circulation time greater than 120 minutes and aortic cross-section time greater than 90 minutes was significantly higher than that in the control group (25.0% vs. 4.1%, p < 0.0001; 16.7% vs. 4.1 %, p=0.0105). In addition, the average tracheal intubation time of patients in the thoracoscopic AVR group was significantly lower than that of the control group (16.13±6.88h vs. 25.01±17.41h, p=0.0029). The average intraoperative blood loss in the thoracoscopic AVR group was significantly lower than that in the control group. The difference was significant (P=0.0017). (142.59 ± 108.56ml vs. 261.08 ± 79.78, P < 0.0001) Similarly, the average postoperative drainage volume of patients in the thoracoscopic AVR group was also significantly lower than that in the control group ( 288.45 ± 201.17ml vs. 399.75 ± 298.08ml, p = 0.0298. ). None of the 48 AVR patients died during hospitalization or within one month after surgery, and there was no significant difference in the incidence of major complications after surgery (8.3% vs. 12.5%, p=0.8987). Conclusion and significance: This study shows that compared with conventional open surgery, total thoracoscopic aortic replacement is feasible, safe, reduces hospitalization time, and achieves better minimally invasive and cosmetic effects, providing support for the promotion of thoracoscopic technology. This initiative has established a solid theoretical foundation and clinical experience and is of great and lasting significance to the scientific community